Image Copy-Move Forgery Detection Algorithms Based on Spatial Feature Domain - Ahmed I.T.; Hammad B.T.; Jamil N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Feature extraction; Signal detection; Support vector machines; Copy-move forgeries; Copy-move forgery detections; Detection accuracy; Image preprocessing; Image processing tools; Mean and standard deviations; Spatial features; State-of-the-art approach; Image processing